Thematic Analysis on COVID-19 Photojournalism in Indonesia - Radityo Widiatmojo; Moch Nasvian Fuad (Universitas Muhammadiyah Yogyakarta, 2021)
The spread of COVID-19 in Indonesia is massive in terms of sufferers. This article aims to seek how national photo news agency ANTARA visualized the pandemic as part of contribution to COVID-19 research in the communication field. By utilizing thematic analysis and qualitative approach, the researchers want to identify, analyze, organize, describe, and report particular themes within an extensive data set of 466 photojournalism. The photos collected from www.antarafoto.com, start from 1 May until 12 May 2020. The finding shows that ANTARA visualized the current Indonesian condition of facing COVID-19 in 8 main themes, determined the countless efforts of ANTARA photojournalists working with a new protocol, and simultaneously also face the new resistance from society. The most popular theme produced by ANTARA photojournalists is economics (183 photos), Social (164), and health (80). Discussion on the most popular is divided into specific topics, namely location, subject’s gender, photographic approach, image format, and news photo category. By utilizing visual ethics on the field, photojournalists communicate the symbols and reality of the real world into a frame to change people’s views about COVID-19 amid the increasingly uncontrolled infodemic flow.